The Cambridge companion to Krautrock - Schütte, Uwe 1967- (Cambridge University Press, 2023)
"Krautrock and its offshoots have had a tremendous impact on musical production and reception in Great Britain and the US since the 1970s. Genres such as indie, post-rock, EDM, and hip-hop have drawn heavily on Krautrock and have connected a music that initially disavowed its European American and African American origins with the lived experience of whites and blacks in the United States and Europe. At the same time, while reaching for an imagined cosmic community, Krautrock, not only by its name, stirs up essentialist notions of national identity and citizenship."
Includes index
Keywords: Krautrock; Krautrock (Music) / History and criticism; Popular music / Germany / History and criticism; MUSIC / General; Aufsatzsammlung